2007
DOI: 10.1345/aph.1k010
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive Therapy in Nonneutropenic Patients with Candida Infection Using the Japanese Guidelines

Abstract: The use of the definitions of clinically documented and possible CI may be beneficial for determining when it is appropriate to initiate preemptive antifungal therapy. However, use of the guidelines did not lead to prevention of possible CI proceeding to clinically documented CI or to improved mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In a study conducted between 1998 and 2002 in a surgical ICU in France [ 70 ], administration of targeted pre-emptive intravenous fluconazole therapy (fluconazole: 800 mg loading dose and then 400 mg/day for 2 weeks) based on colonization indexes was shown to prevent development of proven candidiasis in ICU patients, when compared with an historical control group of patients. A study conducted in Japan examined the effects of early initiation of pre-emptive therapy with an azole (fluconazole or miconazole in 78% and 2% of patients, respectively) or an echinocandin (micafungin in 20%), which was initiated based on a combination of Candida colonization at multiple sites and a positive β-(1,3)-D-glucan test [ 71 ]. The findings indicated that early pre-emptive strategy prevented candidaemia but had no impact on mortality.…”
Section: Antifungal Therapymentioning
confidence: 99%
“…In a study conducted between 1998 and 2002 in a surgical ICU in France [ 70 ], administration of targeted pre-emptive intravenous fluconazole therapy (fluconazole: 800 mg loading dose and then 400 mg/day for 2 weeks) based on colonization indexes was shown to prevent development of proven candidiasis in ICU patients, when compared with an historical control group of patients. A study conducted in Japan examined the effects of early initiation of pre-emptive therapy with an azole (fluconazole or miconazole in 78% and 2% of patients, respectively) or an echinocandin (micafungin in 20%), which was initiated based on a combination of Candida colonization at multiple sites and a positive β-(1,3)-D-glucan test [ 71 ]. The findings indicated that early pre-emptive strategy prevented candidaemia but had no impact on mortality.…”
Section: Antifungal Therapymentioning
confidence: 99%
“…104 Other studies found that it does not reduce the rate of IC infections or mortality (p ¼ 0.33). 105 The current consensus on BDG or other surrogate markers is that they should not alone lead to the initiation of preemptive therapy, mainly due to the low specificity of the marker and the scarcity of its availability. 64 Studies that investigated substantial evidence of Candida spp.…”
Section: Management Of Candida Spp Infections In the Critically Illmentioning
confidence: 99%
“…Indeed, there are currently at least six published treatment guidelines focusing on invasive candidiasis in the non-neutropenic host (Tsuruta et al 2007;Pappas et al 2009a;Aguado et al 2011;Cornely et al 2012;Colombo et al 2013;Alothman et al 2014). Not surprisingly, these recommendations are not overlapping because of differences in interpretation of the published data, variability in local practice, differences in regional epidemiology, individual Candida spp.…”
Section: Guidelines For Treatment Of Candidiasis and Important Gaps Imentioning
confidence: 99%